Between Fancy and Reality: The Crossing of Borders in Poe’s “Ligeia” - Pacini, Lia (Jan Kochanowski University Press, 2023)
The essay aims at exploring the concept of liminality between the borders of reality and fancy, life and death, myth, and fact in Edgar Allan Poe’s short story “Ligeia” (1838). If we envision reality as a line endlessly stretching backward and forward, we might imagine the main female character of the tale, Lady Ligeia, as lingering under or above this line, in someplace other, while the narrator is rooted on this very line of materiality. The woman is both a presence and an absence due to her characteristics as a threshold entity between the world of the living and another realm. The narration extensively hints at elements that lead us to believe that Poe’s protagonist is trying to access, or tirelessly trying to understand, the limits and potentiality of the gateway to the unknown, with Ligeia being an object able to lead him to it. The paper will not only study the metaphysical implications of Ligeia’s persona, but also her interconnection to the world of animals and the mythological links to the siren Lígeia. The last section will deal with the geographical motives of the displacement of the story from a continental area close to the Rhyne to a typical Gothic panorama, such as the English countryside, as a natural mirror to the feelings of loss experienced by the main character.